Simultaneous whole body (18)F-fluorodeoxyglucose positron emission tomography magnetic resonance imaging for evaluation of pediatric cancer: Preliminary experience and comparison with (18)F-fluorodeoxyglucose positron emission tomography computed tomography - Pugmire, Brian S (World J Radiol, 2016)
AIM: To describe our preliminary experience with simultaneous whole body (18)F-fluorodeoxyglucose ((18)F-FDG) positron emission tomography and magnetic resonance imaging (PET-MRI) in the evaluation of pediatric oncology patients. METHODS: This prospective, observational, single-center study was Health Insurance Portability and Accountability Act-compliant, and institutional review board approved. To be eligible, a patient was required to: (1) have a known or suspected cancer diagnosis; (2) be under the care of a pediatric hematologist/oncologist; and (3) be scheduled for clinically indicated (18)F-FDG positron emission tomography-computed tomography (PET-CT) examination at our institution. Patients underwent PET-CT followed by PET-MRI on the same day. PET-CT examinations were performed using standard department protocols. PET-MRI studies were acquired with an integrated 3 Tesla PET-MRI scanner using whole body T1 Dixon, T2 HASTE, EPI diffusion-weighted imaging (DWI) and STIR sequences. No additional radiotracer was given for the PET-MRI examination. Both PET-CT and PET-MRI examinations were reviewed by consensus by two study personnel. Test performance characteristics of PET-MRI, for the detection of malignant lesions, including FDG maximum standardized uptake value (SUVmax) and minimum apparent diffusion coefficient (ADCmin), were calculated on a per lesion basis using PET-CT as a reference standard. RESULTS: A total of 10 whole body PET-MRI exams were performed in 7 pediatric oncology patients. The mean patient age was 16.1 years (range 12-19 years) including 6 males and 1 female. A total of 20 malignant and 21 benign lesions were identified on PET-CT. PET-MRI SUVmax had excellent correlation with PET-CT SUVmax for both benign and malignant lesions (R = 0.93). PET-MRI SUVmax > 2.5 had 100% accuracy for discriminating benign from malignant lesions using PET-CT reference. Whole body DWI was also evaluated: the mean ADCmin of malignant lesions (780.2 + 326.6) was significantly lower than that of benign lesions (1246.2 + 417.3; P = 0.0003; Student’s t test). A range of ADCmin thresholds for malignancy were evaluated, from 0.5-1.5 × 10(-3) mm(2)/s. The 1.0 × 10(-3) ADCmin threshold performed best compared with PET-CT reference (68.3% accuracy). However, the accuracy of PET-MRI SUVmax was significantly better than ADCmin for detecting malignant lesions compared with PET-CT reference (P < 0.0001; two-tailed McNemar’s test). CONCLUSION: These results suggest a clinical role for simultaneous whole body PET-MRI in evaluating pediatric cancer patients.